Impact of The Covid-19 Pandemic on The Psychology of Health Workers - Lezi Mayang Sari; Mufdlilah Mufdlilah; Mamnu’ah (Jurnal Health Sains, 2022)
Corona virus severe acute respiratory syndrome was first released on December 31, 2019 the corona virus spread to many countries around the world. The COVID-19 pandemic has put healthcare workers around the world on the front lines, putting healthcare workers under pressure. The purpose of this study is to review articles regarding the impact of the COVID-19 pandemic on the psychology of health workers. The scoping review obtained data from Pubmed, Sciencedirect and Wiley with Appraisal studies and using Critical Appraisal Hawker, using the PEOs framework. nine articles discuss the impact of psychology on health workers. Anxiety and depression are felt due to fatigue, busy working hours make work results poor and health workers receive less pandemic training. Risk factors for anxiety are fear of infection, community stigma so that health workers feel a lack of social support and no access to mental health services such as psychiatrists. The results of 9 articles that have been reviewed by researchers have the impact of COVID 19 on health workers and risk factors for anxiety during the COVID 19 period. The impact of covid on health workers is anxiety and depression, negative work results and training in handling COVID. The risk factors for anxiety are being a health worker, community stigma and limited access to mental health services.